A Comparative Study in the Level of Environmental Attitude of Students Regarding their Parental Educational Level and Occupation - Ali, Auwalu Rabiu; Endut, Azizah; Embong, Rahimah; Nalado, Aliyu Muhammad (Journal of Science and Technology, 2017)
Environmental attitude is the mental disposition of an individual regarding the environment. It is the attitude of individual towards the environment that guarantees his well-being of that environment. This attitude can be discriminated against the individuals and society via the school system. The present study was conducted to assess the attitude of secondary school students towards the environment. It also studied the differences in the level of the environmental attitude of students based on parental educational level and parental occupation. Moreover, it aimed to find whether age and parental educational level can predict environmental attitude of students. The survey was conducted on 600 respondents from secondary school students who were in Form Four in Terengganu, Malaysia. Simple random sampling was the technique applied in the selection of respondents. Environmental Attitude Questionnaire consisting of 10 items adapted from Hassan Taj Environmental Attitude Scale was employed for the present study. The collected data was analyzed using SPSS version 20. Descriptive and inferential (independents-sample t-test, one-way ANOVA, and Multiple Linear Regressions) statistics were applied to analyze the collected data. The results revealed that the secondary school students have a moderate positive attitude towards the environment. No significant differences were found in the level of the environmental attitude of students based on their parental educational level and parental occupation. The results of regression analyses revealed that the environmental attitude level of students is not associated with their age and their parental educational level.